Aspectos neuroquirúrgicos de las mucopolisacaridosis - Zuccaro, Graciela (Revista Argentina de Neurocirugía, 2020)
Mucopolysaccharidosis is a rare illness that involves the metabolism of mucopolysaccharides, that due to the absence or deficiency of corresponding enzymes, accumulate in almost all the tissues of the body. According to which enzyme is missing, different types of the disease have been identified; the most frequent being Type I with its three variants: Hurler, Hurler-Sheie, and Sheie.Symptoms of this disorder progress and range from mental and physical retardation, multiple skeletal deformities, hepatosplenomegaly, deafness, and corneal opacities among others. Children affected usually appear normal at birth and the slowness in their development may be the first evidence of the disorder whose progression is downhill. Neurosurgical intervention occurs in two pathologies: hydrocephalus that does not show signs of intracranial hypertension and can be confused with atrophy, and cervical cord compression due to storage of mucopolysaccharides in vertebrae, ligaments, and leptomeninges.
Keywords: Glycosaminoglycoside Deposits; Hydrocephalus; Cerebral Atrophy; Cervical Cord Compression